Reducing Potentially Harmful Drug‐Related Problems in Outpatient Prescribing: A Quasi‐Experimental Evaluation of a Multifaceted Clinical Pharmacist Intervention in Vietnam - Thanh‐Tam Le; Thang Nguyen; Minh‐Thy Tran‐Doan; Huong‐Thao Nguyen (JACCP: JOURNAL OF THE AMERICAN COLLEGE OF CLINICAL PHARMACY, 2026)
ABSTRACT Background Drug‐related problems (DRPs) are common in ambulatory prescribing and can cause preventable harm, yet evidence that pharmacist‐led interventions reduce clinically meaningful DRPs in Vietnam remains limited. This study evaluated a multifaceted clinical pharmacist intervention to reduce the prevalence and potential clinical harm of DRPs in adult outpatient prescriptions. Methods We conducted a quasi‐experimental pre‐post study of electronic adult outpatient prescription records at a tertiary hospital in Ho Chi Minh City, Vietnam. Adult outpatient encounters in which patients were prescribed at least two medicines were consecutively sampled during two 14‐day observation periods before and after a 4‐week intervention. The intervention combined prospective prescription review with prescriber feedback, targeted education, and reminders. DRPs were classified using the Pharmaceutical Care Network Europe classification. The primary outcome was the prevalence of prescription records with at least one DRP. Secondary outcomes were DRP density and potentially harmful DRPs assessed by expert‐panel consensus using the Doerper method. Multivariable logistic regression adjusted for prespecified potential confounders. Results A total of 8832 prescription records were analyzed (pre‐intervention, 4586; post‐intervention, 4246). Prescriptions with at least one DRP decreased from 65.7% to 37.3% ( p < 0.001), and mean DRPs per prescription decreased from 1.22 ± 1.24 to 0.55 ± 0.83 ( p < 0.001). Prescriptions with potentially harmful DRPs decreased from 2.4% to 1.7% ( p = 0.04). Reductions occurred across all evaluated DRP subtypes, especially dose selection and administration‐timing problems. After adjustment, the post‐intervention phase remained associated with lower DRP occurrence (adjusted odds ratio, 0.29; 95% confidence interval, 0.26–0.32; the estimated prevalence ratio was 0.57). Conclusion A structured, multifaceted clinical pharmacist intervention was associated with substantial reductions in DRP burden and potentially harmful DRPs in outpatient prescribing. These findings support integrating clinical pharmacists into ambulatory care teams as a scalable medication‐safety strategy in Vietnam and similar resource‐limited health systems.